Biotic Stress Response of Local Host on Cassava Mosaic Virus and its Control with selected Essential Oils: An Experimental Approach - Kiran, Harikumar; Rajalakshmi, Radhakrishnan (Asian Journal of Biological and Life Sciences)
Aim: The present investigation was done to study the antiviral property of essential oils collected from Cymbopogon flexuosus, Ocimum tenuiflorum and Piper nigrum, on local lesion host Gomphrena globosa, which was mechanically infected with Cassava Mosaic Virus (CMV). Materials and Methods: Isolation of essential oil from the aerial parts of Cymbopogon flexuosus, Ocimum tenuiflorum and Piper nigrum was done using GC/MS analysis. The pathogenicity assay was done with the viral inoculum prepared from Mannihot esculenta leaves and was applied to local host, Gomphrena globosa at varying concentrations (100-500 ppm). Further, different biochemical assays like estimation of photosynthetic pigments, flavonoid, proline, MDA and aldehyde were conducted to find out biotic response of local lesion host. Results: It was observed that Concentrated Viral inoculum (CMV-C) was effective in infecting the local lesion host. The local lesion host plant showed many morphological changes like presence of local necrotic lesions, yellowing of leaf and early defoliation of leaves. The yield of the essential oils was 1.4% from C. flexuosus, 0.8% from O. tenuiflorum and 0.6% from P. nigrum dried samples. The most effective oil reducing local lesion number was the oil isolated from C. flexuosus (97.2%), followed by O. tenuiflorum (94.4%) and P. nigrum (91.6 %). Probit analysis data revealed that LC50 value was minimum (133.116 ppm) in C. flexuosus oil where as it was maximum (172 ppm) in P. nigrum oil. From the result it was observed that inhibitory effect of essential oil was dose dependent. Dominant component (>60%) present in O. tenuiflorum and P. nigrum oil was sesquiterpenes. From the three essential oil tested, C. flexuosus oil showed high inhibition activity. Conclusion: Thus, it could be concluded that essential oil from the tested plants can be used to control CMV infection in controlled condition
Keywords: Biotic stress; Cassava mosaic virus; Essential oils; Pathogenicity